Pull-Back Turns, Outside Stops, and Inside Stops Training on Dribbling Skills: Extracurricular Team of State High School - Ishak Ishak; Rusli Rusli; Muh. Adnan Hudain (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Dribbling ability is a fundamental technique in futsal that is often not optimally mastered by extracurricular students, so varied and effective training methods are needed to improve control and speed of players. This study aims to determine the effect of pull back turns, outside stops, and inside stops on the dribbling ability of extracurricular futsal students at High School 5 Barru. This study used a quantitative approach with a quasi-experimental method using a pretest-posttest design with multiple treatment groups. The research subjects were 30 students who were selected using a total sampling technique. The subjects were divided into three treatment groups: pull back turns, outside stops, and inside stops. The instrument used was a futsal dribbling skills test. The treatment was given for 12 meetings, including a pretest session, 10 training sessions, and a posttest. Data was analyzed using descriptive and inferential statistics (paired sample t-test) through SPSS software after fulfilling the prerequisite tests of normality and homogeneity. The results showed that all three types of training had a significant positive effect on dribbling ability (p < 0.05). Descriptive analysis confirmed improved performance, indicated by a decrease in dribbling time from pretest to posttest, across all groups. Pullback turns, outside stops, and inside stops were effective in improving players' control, speed, and dribbling efficiency. The results of this study provide practical insights for futsal coaches and physical education teachers in developing more varied basic technique training programs to improve the performance of school-level athletes.